ROS and Endoplasmic Reticulum Stress in Pulmonary Disease - Cui, Xiangning; Zhang, Yang; Lu, Yingdong; Xiang, Mi (Frontiers in Pharmacology, 2022)
Pulmonary diseases are main causes of morbidity and mortality worldwide. Current studies show that though specific pulmonary diseases and correlative lung metabolic deviance own unique pathophysiology and clinical manifestations, they always tend to exhibit common characteristics including reactive oxygen species (ROS) signaling and disruptions of proteostasis bringing about accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER). ER is generated by the unfolded protein response. When the adaptive unfolded protein response (UPR) fails to preserve ER homeostasis, a maladaptive or terminal UPR is engaged, leading to the disruption of ER integrity and to apoptosis, which is called ER stress. The ER stress mainly includes the accumulation of misfolded and unfolded proteins in lumen and the disorder of Ca2+ balance. ROS mediates several critical aspects of the ER stress response. We summarize the latest advances in of the UPR and ER stress in the pathogenesis of pulmonary disease and discuss potential therapeutic strategies aimed at restoring ER proteostasis in pulmonary disease.